Enhancing Mathematics Teachers’ Competence through Training on Developing Interactive Learning Media Based on ClassPoint AI - Anny Sovia; Partasiwi, Nurashri; Haeruman, Leny Dhianti; El-Hakim, Lukman; Siska; Pratama, Haikal Dito (Jurnal Pengabdian Masyarakat Inovatif, 2025)
This training program aimed to enhance the pedagogical competencies of Mathematics teachers at Madrasah Aliyah (Islamic Senior High Schools) in Jakarta Special Capital Region in utilizing ClassPoint AI technology to develop interactive learning media. The training methodology incorporated lecture-based instruction, live demonstrations, hands-on practice sessions, and group discussions. Participants comprised 26 mathematics educators affiliated with the Mathematics Subject Teachers' Forum (MGMP). Evaluation results demonstrated significant improvement in participants' mastery of ClassPoint features, with a mean satisfaction rating of 4.43 out of 5. Primary implementation challenges included technological infrastructure limitations and internet connectivity issues. The training successfully promoted technology integration in instructional practices, aligning with Sustainable Development Goal (SDG) 4 objectives regarding quality education. Recommendations for subsequent training iterations include the development of simplified installation modules and extension of program duration to optimize learning outcomes.